MichaelWalzer’s Humanitarian Intervention Theory Applied to Multisided Conflicts: A Discussion of Intervention and Self-Determination in the Syrian CivilWar (2020)
Humanitarian interventions have often been employed to promote the intervener’s political and economic interests. Given the issues around intervention’s morality, this article explores MichaelWalzer’s humanitarian intervention theory in order to unravel the practical di culties of legitimating humanitarian interventions in multisided conflicts. After exploring Walzer’s arguments as they relate to unilateral and multilateral interventions, this article explains why, according to the self-determination principle, intervening countries must share the victim’s cause. Later, the article uses the Syrian CivilWar to exemplify the conundrum of crafting a legitimate humanitarian intervention in multisided conflicts where the victims are internally divided and have opposing political, economic, and/or religious views. This case study evidences how, in such contexts, humanitarian interventions simultaneously protect the population and promote the group that best represents the intervening state’s interests, thus turning internal conflicts into foreign proxy wars. Finally, the article argues that, despiteWalzer’s proposal for a consistent theory of unilateral and multilateral humanitarian interventions, unilateral interventions should be replaced in multisided conflicts by multilateral interventions able to halt atrocities and provide a stable solution for internal conflicts. Keywords: humanitarian intervention; MichaelWalzer; Syria; Civil War; self-determination